Effects of particle size of hydroxyapatite on mechanical property and cytocompatibility of hydroxyapatite/poly(amino acid) composites. Issue 2 (14th December 2021) - Lyu, Defu; Zhang, Qiyi; Wu, Yanan; Chen, Lichao; Li, Xiaodan; Ren, Haohao; Yan, Yonggang
Abstract: In this work, three different particle sizes of hydroxyapatites (HA) were synthesized, and these three types of HA were combined with poly(amino acid) (PAA) to form composites (PAA/HA) by phase separation technique. XRD, FT‐IR, SEM, EDS, and XPS analyses were utilized to characterize the structure and morphology of the synthesized three HA particles and composites. Results revealed that HAs with three different particle sizes (short rod (HA1), long rod in nanoscale (HA2), and long rod in micron level (HA3)) were successfully prepared and there was an interface interaction between PAA and HA in composites. Mechanical tests showed that the difference of HA in size played an important role in mechanical performance of the composites. Furthermore, the long rod nano‐HA showed the highest enhancement in flexural yield strength at 81.3% for PAA/HA2 compared with pure PAA. After 28 days of immersion in PBS, PAA, and its composites showed good stability, and the mechanical performance of all composites were remained unchanged. The cell culture results showed all composites were cytocompatible, cells attached on the materials well with excellent morphology. Thus, it could be concluded that particle size influenced mechanical properties of PAA/HA composites, without impacting their cytocompatibility and degradation behavior. Abstract : In this work, three types of HA were combined with poly(amino acid) (PAA) to form composites (PAA/HA). Particle size influenced mechanical properties of PAA/HA composites, without impacting their cytocompatibility and degradation behavior.